On the texture formation of selective laser melted Ti-6Al-4V - Simonelli, Marco; Tse, Yau Yau; Tuck, Christopher (Springer, 2014)
Selective laser melting (SLM) has been shown to be an attractive manufacturing route for the production of α/β titanium alloys. The relationship between the SLM process parameters and the microstructure of titanium alloys has been the object of several works, but the texture formation during the SLM process has yet to be understood. In the present study, the texture formation of Ti-6Al-4V components was investigated in order to clarify which microstructural features can be tailored during the SLM process. The microstructural characterization of the as-built components was carried out using various microscopy techniques. Phase and texture analysis were carried out using backscattered electron imaging and diffraction. It was found that as-built components consist exclusively of α’ martensitic phase precipitated from prior β columnar grains. The texture of the prior β phase was reconstructed and discussed in relation to the used SLM process parameters. It was found that the β grain solidification is influenced by the laser scan strategy and that the β phase has a strong <100i> texture along its grain growth direction. The α’ martensitic laths that originate from the parent b grains precipitate according to the Burgers orientation relationship. It was observed that α’ laths clusters from the same β grain have a specific misorientation that minimizes the local shape strain. Texture inheritance across successive deposited layers was also observed and discussed in relation to various variant selection mechanisms